The politics of nonsense: civil unrest, otherness and national mythology in nonsense literature - Shortsleeve, KK (2007)
This study argues that the generative qualities of nonsense literature that foster in the reader a rebellious, anti-authoritarian spirit have been underestimated. At characteristic moments of social unrest the popularity of nonsense literature rises and texts that utilise the mores and tropes of nonsense are enlisted in support of radical causes. Nonsense participates in the genesis of a new political paradigm that is incommensurable with the old, serving as a popular coded representation, and as a vehicle for the propagation, of new concepts, beliefs and ideologies. These “characteristic moments” of social unrest are akin to the historical situation that Mikhail Bakhtin requires for a flourishing of carnivalesque imagery. Nonsense, like Bakhtin’s carnivalesque, is invigorated by “moments of crisis, of breaking points in… the life of society and man” (Bakhtin, Rabelais 9). Because of its close association with carnivalesque imagery, nonsense is normally situated in a convivial, democratic atmosphere. As Bakhtin posits, this carnivalesque milieu fosters an atmosphere that revels in the expression of political criticism and utopian ideals (ibid 92-3). Revisiting Elizabeth Sewell’s contention that nonsense rejects magic and superstition (Sewell 171-72), I suggest instead a two-part process. Nonsense first rejects commonly accepted, but arbitrary, systems of authority and then, through subversive allusions to an alien alternative, nonsense subtly advertises the desirability of unofficial belief systems. In nonsense texts, symbols of unofficial belief systems are routinely combined with inexplicable narrative voids and temporal anomalies that tempt the reader to envision a temporary release from constrictive conceptions of society and the self. Nonsense thus plays a pivotal role in the language, culture and mythology of revolution. This process, which allies nonsense to radical causes in times of social upheaval, is one of the major sources of the popular success of icons of children’s literature such as Mother Goose, Lewis Carroll and Dr. Seuss. Because nonsense is not restricted to texts intended for children, neither is this study. The political aspects of nonsense will be the more holistically examined by inclusion in this discussion of, for example, the political satire of eighteenth century colonial American humorist Francis Hopkinson, the Victorian era libretti of W. S. Gilbert, and the lyrics of 1960s era songwriters John Lennon and Bob Dylan.